Italian neonatologists and SARS-CoV-2: lessons learned to face coming new waves - Cavicchiolo, Maria Elena (Pediatr Res, 2021)
ABSTRACT: The aim of this review was threefold: (a) to retrieve all SARS-CoV-2 evidences published by Italian neonatologists working in maternity centers and NICUs during the pandemic; (b) to summarize current evidence for the management of term and preterm infants with a SARS-CoV-2-related illness; and (c) to provide an update for dealing with the second wave of COVID-19 and discuss open questions. A review was conducted using MEDLINE/PubMed and the national COVID-19 registry of the Italian Society of Neonatology including citations from December 1, 2019 to October 28, 2020. Sixty-three articles were included. Collected data were divided into the following topics: (a) antenatal management, (b) management in delivery room, (c) postnatal management, (d) mother–baby dyad and breastfeeding management, (e) neonatal emergency transport system reorganization, (f) parents’ management and perspective during SARS-CoV-2 pandemic, and (g) future perspective. Evidences have evolved over the pandemic period and the current review can be useful in the management of the mother–neonate dyad during SARS-CoV-2 future waves. Italian neonatologists have played an active role in producing official guidelines and reporting data that have contributed to improve the care of neonates. A joint European action plan is mandatory to face COVID-19 in neonates with more awareness. IMPACT: A joint European action plan is mandatory to face COVID-19 in neonates with more awareness. This review summarizes the available evidences from neonatal COVID-19 management in Italy analyzing all the published paper in this specific field of interest. The current review can be useful in the management of the mother–neonate dyad during the SARS-CoV-2 future waves.